A qualitative exploration of postgraduate students’ and lecturers’ perspectives on whether their experiences of higher education reflect an ‘Intellectually Humble Dialogic Space’ - Godfrey, H (2020)
My dissertation explores whether self-reported experiences of higher education from lecturers and postgraduate students reflect an ‘intellectually humble dialogic space’; this is a conceptual space representing a disposition to rigorously consider opposing ideas to beliefs held, where ideas are presented in a manner where they are rigorously considered to be true relative to alternatives; finally, it is a space where participants incorporate the most truthful ideas in developing their deeply held beliefs.